2017
DOI: 10.29015/cerem.410
|View full text |Cite
|
Sign up to set email alerts
|

Public Pension Fund Structure And Mechanisms: A Case Study Of The Tanzanian Pension Funds System

Abstract: Abstract:Aim: Good governance structures have become an issue of public interest, including public pension systems. The quality and performance of the trustees of the funds influences the income flows to which members are entitled and promised, as well as any shortfalls thereof that may require interventions. We aim to examine the pension fund governance in Tanzania, by focusing on structures and mechanisms of boards of trustees, as well as its perceived challenges and future directions. Design / Research meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Furthermore, the study highlighted that comprehensive investment policies established by pension fund boards had a positive correlation with investments in equities, foreign assets, and lower cash holdings. Mpinga and Westerman (2017) conducted a literature review to develop a comprehensive framework for studying the governance of pension funds, encompassing both the macro (regulatory) and micro (board of trustees) levels. The study emphasized the pivotal role played by the board of trustees in pension fund governance, and observed that the pension fund structure and mechanisms in Tanzania adhere to high standards.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Furthermore, the study highlighted that comprehensive investment policies established by pension fund boards had a positive correlation with investments in equities, foreign assets, and lower cash holdings. Mpinga and Westerman (2017) conducted a literature review to develop a comprehensive framework for studying the governance of pension funds, encompassing both the macro (regulatory) and micro (board of trustees) levels. The study emphasized the pivotal role played by the board of trustees in pension fund governance, and observed that the pension fund structure and mechanisms in Tanzania adhere to high standards.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The board of directors has the prime responsibility to oversee the success of the pension fund managers by making strategic decisions that will help the pension fund managers to survive for many years. Mpinga and Westerman (2017) support this position by proposing that a strong (well-informed) board is needed to drive an organisation's vision with a good sense of judgment in management and performance. McCahery et al (2016) recommended in their study that shareholders must tie the remuneration of board members to their performance.…”
Section: Dominant Corporate Governance Practices Of Pension Fundsmentioning
confidence: 99%
“…A review of the literature revealed that the relationship between corporate governance practices and the management of pension funds is not clear in research outlets in Ghana (Dorfman 2015;Mpinga and Westerman 2017). As in other emerging economies (Dorfman 2015;Mpinga and Westerman 2017;Phan and Hegde 2012), the pension industry in Ghana is still evolving due to the limited income of the labour force, which is not interested in setting aside funds to cater for pensions (Stewart and Yermo 2009). Numerous factors have been identified as accounting for this phenomenon, which include including an aging population, income disparities, mismanagement of pension funds, political interference, and low investment returns (Anku-Tsede 2019).…”
Section: Introductionmentioning
confidence: 99%